Beyond health system contact: measuring and validating quality of childbirth care indicators in primary level facilities of northern Ethiopia - Haftom Gebrehiwot Weldearegay; Araya Abrha Medhanyie; Hagos Godefay; Alemayehu Bayray Kahsay (BMC, 2020)
Abstract Background Measurement of quality of health care has been largely overlooked and continues to be a major health system bottleneck in monitoring performance and quality to evaluate progress against defined targets for better decision making. Hence, metrics of maternity care are needed to advance from health service contact alone to content of care. We assessed the accuracy of indicators that describe the quality of basic care for childbirth functions both at the individual level as well as at the population level in Northern Ethiopia. Methods A validation study was conducted by comparing women's self-reported coverage of maternal and newborn health interventions during intra-partum and immediate postpartum care received in primary level care facilities of Northern Ethiopia against a gold standard of direct observation by a trained third party (n = 478). Sensitivity, specificity and individual-level reporting accuracy via the area under the receiver operating curve (AUC) and inflation factor (IF) to estimate population-level accuracy for each indicator was applied for validity analysis. Findings 455(97.5%) of women completed the survey describing health interventions. Thirty-two (43.2%) of the 93-basic quality child birth care indicators that were assessed could be accurately measure at the facility and population level (AUC > 0.60 and 0.75 < IF< 1.25). Few of the valid indicators were: whether women and their companion were greeted respectfully, whether an HIV test was offered, and whether severe bleeding (hemorrhage) was experienced by the woman. An additional 21(28.4%) indicators accurately measure at the facility or individual level, but the indicators under or over estimate at population level. Thirteen other indicators could accurately measure at population level. Eight (8.6%) indicators didn't meet either of the validity criteria. Conclusion Women were able to accurately report on several indicators of quality for basic child birth care. For those few indicators that required a technical understanding tended to have higher don't know response from the women. Therefore, valid indicators should be included as a potential measurement of quality for the childbirth care process to ensure that essential interventions are delivered.